Fixed Point and Common Fixed Point Results of \(D_F\)-Contractions via Measure of Non-compactness with Applications - Ullah, Asmat; Khan, Israr Ali; Mehmood, Nayyar (Communications in Mathematics and Applications, 2018)
In this paper, we study a new contraction mapping inspired by the concept of \(F\)-contraction, which was recently introduced by Wardowski [20]. We find common fixed points for a sequence of mappings by introducing \(D_F\)-contractive operators in Banach space using the concept of measure of non-compactness. As an application, we prove some results on the existence of solutions for a system of an infinite fractional order differential equations in the space \(c\), where space \(c\) consists of real sequences having the finite limits.